2012
DOI: 10.1073/pnas.1118514109
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic transgenerational inheritance of altered stress responses

Abstract: Ancestral environmental exposures have previously been shown to promote epigenetic transgenerational inheritance and influence all aspects of an individual's life history. In addition, proximate life events such as chronic stress have documented effects on the development of physiological, neural, and behavioral phenotypes in adulthood. We used a systems biology approach to investigate in male rats the interaction of the ancestral modifications carried transgenerationally in the germ line and the proximate mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(219 citation statements)
references
References 44 publications
5
206
0
1
Order By: Relevance
“…This idea is the intellectual foundation of the search for heritable histone modifications, DNA methylation, etc., yet is rarely directly tested. Strikingly, and underscoring our concern, in a few cases where data have been presented, the idea of allelespecific memory is either not tested or is directly refuted (Anway et al 2005;Pembrey et al 2006;Greer et al 2011;Crews et al 2012;Stern et al 2012;Voutounou et al 2012;Buescher et al 2013;Padmanabhan et al 2013;Wan et al 2013;Gapp et al 2014).…”
Section: The Test(s)mentioning
confidence: 99%
“…This idea is the intellectual foundation of the search for heritable histone modifications, DNA methylation, etc., yet is rarely directly tested. Strikingly, and underscoring our concern, in a few cases where data have been presented, the idea of allelespecific memory is either not tested or is directly refuted (Anway et al 2005;Pembrey et al 2006;Greer et al 2011;Crews et al 2012;Stern et al 2012;Voutounou et al 2012;Buescher et al 2013;Padmanabhan et al 2013;Wan et al 2013;Gapp et al 2014).…”
Section: The Test(s)mentioning
confidence: 99%
“…It is well known that adverse environments can significantly alter the epigenome and such modifications have been associated with several psychiatric disorders (Gräff and Mansuy, 2009;Ptak and Petronis, 2010;Tsankova et al, 2007). Recent work has shown that these environmentally-mediated epigenetic changes can be inherited through the paternal line and this can potentially have consequences on the inheritance of psychiatric disorders (Crews et al, 2012;Gapp et al, 2014). This emphasizes the need to identify not only genetic factors, but also environmental influences on the epigenetic mechanisms that may contribute to this inheritance of predisposition to mental illness (Toth, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These altered expression patterns correlated with sex-specific altered anxiety-like behaviours up to the F3 generation [60]. The vinclozolin exposure three generations earlier even altered the murine response to chronic restraint stress [61].…”
Section: Epigenetics and Diseasementioning
confidence: 90%